The conserved oligomeric Golgi (COG) complex, a window into plant-pathogen interactions - Klink, Vincent P.; Lawaju, Bisho R.; Niraula, Prakash M.; Sharma, Keshav; McNeece, Brant. T.; Pant, Shankar R.; Troell, Hallie A.; Acharya, Sudha; Khatri, Rishi; Rose, Alexandra Hammett; Alkharouf, Nadim W.; Lawrence, Kathy S. (Journal of plant interactions, 2022)
The endomembrane system, functioning in secretion, performs many roles relating to eukaryotic cell physiological processes and the Golgi apparatus is the central organelle in this system. An essential associated Golgi component is the conserved oligomeric Golgi (COG) complex, maintaining correct Golgi structure and function during retrograde trafficking. In animals, naturally occurring cog mutants provide a window into understanding it's function(s). Eliminating even one COG component impairs its function. In animals, COG mutations lead to severe cell biological and developmental defects and death while far less is understood in plants which is changing. The plant genetic model Arabidopsis thaliana COG complex functions in growth, cell expansion and other processes, involving direct interactions with other secretion system components including the exocyst, soluble N-Ethylmaleimide-Sensitive Factor Attachment Protein Receptor (SNARE), and the microtubule cytoskeleton. Recent experiments have identified a defense role for the COG complex in plants, the focus of this review.